Eucommia ulmoides bark extract reduces blood pressure and inflammation by regulating the gut microbiota and enriching the Parabacteroides strain in high-salt diet and N(omega)-nitro-L-arginine methyl ester induced mice - Yan, Dong; Si, Wenhao; Zhou, Xiaoyue; Yang, Mengjie; Chen, Yuanhang; Chang, Yahan; Lu, Yidan; Liu, Jieyu; Wang, Kaiyue; Yan, Moyu; Liu, Feng; Li, Min; et al. (Frontiers in Microbiology, 2022)
Hypertension is a major threat to human health. Eucommia ulmoides Oliv. (EU) is an herb widely used to improve hypertension in East Asia. However, its major constituents have poor absorption and stay in the gut for a long time. The role of gut microbiota in the anti-hypertensive effects of EU is unclear. Here, we examined the anti-hypertensive effects of EU in high-salt diet and N(omega)-nitro-L-arginine methyl ester (L-NAME) induced mice. After receiving EU for six weeks, the blood pressure was significantly reduced and the kidney injury was improved. Additionally, EU restored the levels of inflammatory cytokines, such as IL-6 and IL-17A from blood serum, and IL-17A from kidney. The diversity and composition of gut microbiota were influenced by administration of EU. Thus, 40 significantly upregulated and 107 significantly downregulated amplicon sequence variants (ASVs) were identified after administration of EU. ASV403 (Parabacteroides) was selected as a potential anti-hypertensive ASV and its closest strain XGB65 was isolated. Furthermore, animal studies confirmed that Parabacteroides strain XGB65 exerted anti-hypertensive effects possibly through reducing levels of inflammatory cytokines, such as IL-17A from kidney. Our work first reports that EU reduces the blood pressure through regulating gut microbiota and its enriched Parabacteroides strain exerts the anti-hypertensive effects, which provides novel solutions for developing new anti-hypertensive treatments through combining probiotics and prebiotics.